2022
DOI: 10.1113/ep090315
|View full text |Cite
|
Sign up to set email alerts
|

The miRNA‐143‐3p–Sox6–Myh7 pathway is altered in obesogenic diet‐induced cardiac hypertrophy

Abstract: Obesity induces cardiometabolic disorders associated with a high risk of mortality. We have previously shown that the microRNA (miRNA) expression profile is changed in obesity-induced cardiac hypertrophy in male mice. Here, we investigated the effect of an obesogenic diet on the expression of miRNAs involved in cardiac hypertrophy in female mice. Female mice fed an obesogenic diet displayed an increased body weight gain, glucose intolerance, insulin resistance and dyslipidaemia. In addition, obese female mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…These results suggest that miR-24-3p may regulate skeletal muscle fiber type transformation by binding to these gene clusters ( Mapk14 , Nek4 , Pskh1 , Pim1 , and Nlk ). Furthermore, it has been shown that many genes are involved in skeletal muscle regeneration and myofiber type transformation, such as MEETL8 and SOX6 inhibiting slow myogenesis by suppressing MYH7 expression [ 66 , 67 ], and Map3k20 and LSD1 playing important roles in regulating skeletal muscle regeneration [ 68 , 69 ]. We speculate that miR-24-3p may also target these genes in regulating myofiber type transformation and skeletal muscle regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that miR-24-3p may regulate skeletal muscle fiber type transformation by binding to these gene clusters ( Mapk14 , Nek4 , Pskh1 , Pim1 , and Nlk ). Furthermore, it has been shown that many genes are involved in skeletal muscle regeneration and myofiber type transformation, such as MEETL8 and SOX6 inhibiting slow myogenesis by suppressing MYH7 expression [ 66 , 67 ], and Map3k20 and LSD1 playing important roles in regulating skeletal muscle regeneration [ 68 , 69 ]. We speculate that miR-24-3p may also target these genes in regulating myofiber type transformation and skeletal muscle regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA deregulation is frequent during CH [25]. As an example, miR-143-3p is related to the development of CH induced by an obesogenic diet [26]. Moreover, targeting miR-30b has been proposed as a potential therapy in CH [27].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in MYH7 and MYH7B expression and/or transcriptional activity is one of the cascade effects associated with SOX6 inhibition that has been described either in vitro or in animal models. [ 18 , 19 ]. It has been postulated that increased MYH6 leads to upregulation of miR-208a , which in turn inhibits the expression of SOX6 but promotes the activation/upregulation of MYH7B , with subsequent upregulation of miR-499, which is another modulator of SOX6 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%